The difficulty in determining the Malays, in accordance to the definition given in the Federal Constitution / Shamsul Bahrin Baharuddin - Baharuddin, Shamsul Bahrin (Faculty of Law, 1982)
The purpose of this paper is to make a modest attempt to present the difficulty in determining whether one is a Malay or not if the definition of Article 160 (2) is to be the test. The difficulty may arise in the granting of the special privileges of the Malays. It is firstly submitted that it is never intended to be argued whether the Malays have the right to the special privileges or not as these rights are unambiguously laid down in Federal Constitution. The 1 Malays 1 discussed in this paper is confined to the Malays in Peninsula Malaysia only so as to keep the project paper from covering too wide an area.